Analisis Pelayanan Pasien Rawat Jalan Pada Program Badan Penyelenggara Jaminan Kesehatan Pada Rumah Sakit Umum Haji Medan - Herlina Wati Pasaribu; Irwan Nasution; Armansyah Matondang (Universitas Medan Area, 2021)
Health is important to everyone. Health efforts are aimed at improving service quality, equity and reach of health services. The presence of the Social Security Administration Agency (BPJS) of Health proves the seriousness of the Government in providing health services for all Indonesians and provides an alternative to using health insurance. The purpose of this study is To analyze the Service On Outpatient Patients In BPJS Program at Medan Haji General Hospital. The research method used in this research is quantitative descriptive method Samples in this study amounted to 100 outpatients of BPJS participants, who were taken accidentally (within 10 days). Technique of collecting data there are two primary data and secondary data of primary data is done by Questionnaire, Interview, and Observation. Secondary Data Collection Techniques, namely Documentation, Library Studies, Descriptive statistical analysis techniques. The result of the outpatient service at Haji Hospital Medan was classified the answer where the good service was 15 people (15,0%), the good service was 79 people (79,0%), and the bad service was 6 people (6,0 %). Can be dismpulkan that service at Haji Hospital Medan is good enough.